Combination of xanthan gum and HPMC as retardants in sustained release gliclazide formulation - Othman, Liyana Zafirah; Mohd Nawi, Mohamed Sufian; Abul Bashar Mohammed, Helaluddin; Elsayed, Tarek Mohamed Ali (2017)
Gliclazide tablet is widely used for the treatment of non-insulin-dependent diabetes mellitus. However, there is still lack of study done in formulating the sustained release gliclazide tablet. Combination of xanthan gum, a natural gum and hydroxypropyl methylcellulose (HPMC) were used to act as retardants for the sustained release gliclazide tablet. In this study, sustained release 60 mg gliclazide tablets were formulated with different ratios and content of xanthan gum and HPMC. The tablets were produced by wet granulation and semi-automatic tableting process. The content variation, weight variation, hardness, and friability of the tablet met the specification by British Pharmacopoeia. In vitro dissolution profiles of the tablets were compared with the commercially available sustained release 60 mg gliclazide tablet.